Pengalaman pemberian ASI ekslusif pada Ibu bekerja: scoping review - Dinar Agustin; Andari Wuri Astuti (Universitas Ahmad Dahlan, 2021)
Working mothers faced many challenges and constraints. Despite legislations mandating workplaces to give support, including breastfeeding areas for their employees, a number of hurdles remained, preventing them from achieving exclusive breastfeeding (EBF). Therefore, this review intended to review evidence on the experience of EBF practices among working mothers. This study employed scoping review by using four stages. Firstly, develop the focus of the study through the framework of PEOS (Population, Exposure, Outcome and study design). Secondly, conducted literature search using three relevant databases (PubMed, Science Direct, Wiley Online) and grey literature (Google scholar). Thirdly, selected relevant studies using inclusion and exclusion criteria. Fourthly, conducted critical appraisals using data charting to assess the quality of included articles, followed by analyzing and reporting the results. PRISMA flowchart was used to describe the literature search plot. Based on 12 included articles, twothirds of the included articles were qualitative studies categorized as grade A. The other four articles had grade B where three out of four were non-randomized quantitative studies and one mixed-method study. Some factors identified to be the cause to prevent continued EBF were insufficiency support and facilities from family, husband, coworkers in the workplaces (paid leave, availability of daycare, lactation room, breast milk pumping tools). Two other identified factors were previous breastfeeding experience and knowledge. The implementation of EBF practices were challenging in some developed countries. However, having good knowledge was necessary to reduce the gap between maternal perception and belief in which was occurred in Italy study. In contrary, low knowledge was found as an important obstacle in the developing world such as Bangladesh. Overall, perception and belief related to EBF of working mothers contributed to the practice of EBF.